Healing Dramas: Divination and Magic in Modern Puerto Rico by Raquel Romberg - Mulligan, Jessica (American Anthropologist, 2011)
Healing Dramas opens with a provocative contradiction about the problem of belief. The clients who consult spiritual mediums in Puerto Rico often claim that they do not believe in magic and witchcraft but nonetheless are convinced that it works (p. 8). By focusing her ethnography on the phenomenological side of ritual, Raquel Romberg shows how healers create drama-filled consultations, craft their reputations, and conduct cleansing rituals that are “transformative, healing, and reconstitutive” (p. 95). In the end, this ethnographic exploration of magic practices in Puerto Rico succeeds in revealing what makes magic rituals compelling, irrespective of belief. Healing Dramas is the second book to emerge from Romberg's fieldwork in Puerto Rico that was conducted from 1995–96. The first book, Witchcraft and Welfare: Spiritual Capital and the Business of Modern Magic in Puerto Rico (Romberg 2003), combined historical research with ethnography to trace how witchcraft developed on the island from its persecuted Spanish colonial past to the modern context in which “spiritual entrepreneurs” operate in a laissez-faire environment where their magic works help clients achieve spiritual, material, and emotional success. Her newer work, Healing Dramas, focuses on the “formal and phenomenological side of ritual experiences, personal stories, dreams, and [Romberg's] own reflections” (p. 1). In this book, the emphasis is on the ritual, performative, and sensual aspects of the practice of brujería (witchcraft) rather than its more sociopolitical, historical, and economic context. As such, the book is thoroughly reflexive; it is “as much about brujos (witch-healers) and the drama of divination and magic rituals as about fieldwork, ethnography, and [Romberg's] reflections about them” (p. xi). The book's content and organization mimic the “energetic-moral ethos of Spiritism” (p. 13); it is organized around the following: dreams, drama, spiritual time, the sentient body, and space. Each of these aspects of Spiritism is essential to the form and function of divination and witchcraft in Puerto Rico—they each make magic ritual “work.” For example, sharing and interpreting dreams is an important component of Spiritism because dreams are thought to contain messages from other worlds (p. 42), and the chapter on space catalogs the sacred spaces involved in witchcraft with explanations of their significance and meaning. A major strength of this work is its basis in long-term ethnographic fieldwork. The relationships that Romberg developed with various healers on the island were clearly deep and meaningful. She trained with several healers long enough to be gradually let in on many of their secrets (some of which she reveals to the reader and others she does not). Another strength is the book's focus on the “eclectic religious atmosphere” (p. 2) that Romberg encountered in Puerto Rico, where Spanish Catholicism, U.S. Protestantism, Spiritism, Santería, new age practices, self-help discourse, and even elements of popular consumer culture were creatively combined in sometimes surprising ways. Romberg's use of extensive transcripts from taped conversations that evoke ritual performance as well as her use of photographs, especially ones that document ritual progression, likewise strengthen the work. Finally, the book benefits from the inclusion of personal reflections on the process of conducting fieldwork (such as dreaming while in the field and moments when Romberg herself was perceived by others as a witch). One aspect of the book that is perplexing, however, is the use of cross-cultural examples. In the chapter on dreams, for instance, the cross-cultural literature on dreaming is discussed in detail. However, its relevance to witchcraft and healing in Puerto Rico is not entirely clear. Is Romberg arguing that there are universal approaches to dreaming and dream interpretation? What do the Arapesh of northern New Guinea or residents of Naxos, Greece, offer to the interpretation of dream narratives in Puerto Rico (see pp. 48–49)? The many forays into comparative cases distract from the flow of the narrative and undermine Romberg's stated intention to write evocative, sensual descriptions of ritual practice. Rather than an exhaustive discussion of anthropological research on dreaming, a more targeted approach to the literature would have been preferable. Healing Dramas will appeal to scholars of the Caribbean, of witchcraft and magic, and of vernacular religion. The book is also likely to be of interest to students of postcolonial theory given the provocative argument that the thoroughly entrepreneurial form of witchcraft that is practiced in Puerto Rico functions to “reproduce, not subvert, the modern colony, even though unwillingly and in oblique ways” (p. 5